SIMULASI SISTEM PROTEKSI MOTOR INDUKSI 3 FASA TERHADAP SUPLAI TEGANGAN TIDAK SEIMBANG DENGAN METODA SIMULINK - I Kadek Dwi Artika Putra; Wayan Arta Wijaya; I Gusti Ngurah Janardana (Jurnal SPEKTRUM, 2021)
The most widespread use of AC electric motors is three-phase induction motors, almost90% of motor applications in the industry use three-phase induction motors. The operation of 3phase induction motors generally has voltage imbalance disorders. Voltage imbalance affectsseveral things, including losses and efficiency. This study uses simulation method with the aimto determine the influence of unbalanced voltage on the characteristics of 3 phase inductionmotor and how to secure a 3-phase induction motor when it gets an unbalanced voltage supply.The result of this simulation obtained the smallest efficiency is 56.8% in the voltage dropcondition in one phase and 78.4 in the voltage drop condition in all three phases (R, S and T)with voltage asymmetry of 20% and the biggest loss is 11 406 Watts in the voltage dropcondition on one phase with voltage asymmetry of 20%. In the simulation of 3 phase inductionmotor protection system of unbalanced voltage supply obtained by tripping breaker fastest thatis at 0.201 s seconds with drop voltage condition 15% in phase S. 3 phase induction motorsafety pattern when getting unbalanced voltage supply is to use an unbalanced voltage safetysystem that has faster tripping delay time.